Sexual harassment and its impact on emotions among adolescents in Sabah, Malaysia: An exploratory study - Balan Rathakrishnan; Azizi Yahaya; Soon Singh Bikar Singh (Hong Kong Journal of Social Sciences, 2022)
Sexual harassment has been one of the most pointed and hotly debated issues this decade. Therefore, this study aims to determine adolescents’ perception of sexual harassment and its impact on emotions. This study used quantitative methods where the data was obtained through the questionnaire survey, which consisted of the Sexual Experiences Questionnaire and Emotion Regulation Questionnaire, where 400 adolescents participated. The data were analyzed using the Statistical Packages for the Social Sciences (SPSS) application. Pearson correlation was used to explain the relationship between the two variables, adolescents’ perceptions towards sexual harassment and its impact on emotions. The results show that 208 adolescents had experienced sexual harassment, and most of them were female respondents. This study found a significant relationship between adolescents’ experiences of sexual harassment and their perceptions of sexual harassment. Besides, the relationship between adolescents’ experiences of sexual harassment and its impact on emotions also showed significant value. Therefore, this indicates that sexual harassment experiences significantly affected the victims’ perceptions and emotions. Sexual harassment is violence and, effective action must be taken to address the sexual harassment issue. Moreover, this study will benefit communities and adolescents about sexual harassment and its effect on their emotions.